Exploring assignment plagiarism by students in private colleges in China - Chen, Lin; Saharuddin, Norzihani (Secholian Publication, 2023)
This study explored influence factors and solutions to assignment plagiarism among private college students in China. The focus of this study was two: i) To explore the influence factors contributing to assignment plagiarism of Chinese private college students and ii) To explore the solutions to assignment plagiarism of Chinese private college students. This study employed a qualitative method with a case study design and posted a series of one-on-one semi-structured interviews with six graduates from private colleges in China. Twenty-one graduates applied, but only six of them met the criteria. This study adopted thematic analysis to explore participants' responses. This study reported that researchers found ten themes identified in this study of research question one. They are students with weak learning foundations; students expect to receive learning rewards; students hope for better development in the future; students do not judge and understand the standard of assignment plagiarism; lecturers lack guidance and supervision of students; lecturer assignments design is not reasonable; and others. Night themes were identified in this study of research question two: changing students' learning styles, stimulating interest in learning, and advocating independent learning; improving the quality of teaching and learning and laying a solid foundation for students after graduation; strengthening education on academic integrity and academic norms; improve lecturers' academic advising and supervisory skills; reasonable setting of assignments and establishment of good rules for assignment management and evaluation; and so on.